2009
DOI: 10.1002/jhm.496
|View full text |Cite
|
Sign up to set email alerts
|

U.S. physician satisfaction: A systematic review

Abstract: INTRODUCTION:There is concern in the US about the burden and potential ramifications of dissatisfaction among physicians. The purpose of this article is to systematically review the literature on US physician satisfaction.METHODS:A MEDLINE search with the medical subject headings (MeSH) phrases: (physicians OR physician's role OR physician's women) AND (job satisfaction OR career satisfaction OR burnout), limited to humans and abstracts, with 1157 abstracts reviewed. After exclusions by 2 independent reviewers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
132
3
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(168 citation statements)
references
References 89 publications
18
132
3
10
Order By: Relevance
“…We first performed a systematic review of US physician satisfaction to identify previous relevant research and key study domains. 15 The 16-member SHM Career Satisfaction Task Force served as a focus group to appraise physician job satisfaction measures and other worklife domains (e.g., workload, work-life balance) for their applicability to hospitalists. An expert panel (TBW, KH, CTW) synthesized the focus group's discussion to generate 14 domains most pertinent to current hospitalist job satisfaction which were further refined through multiple discussions in the focus group.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…We first performed a systematic review of US physician satisfaction to identify previous relevant research and key study domains. 15 The 16-member SHM Career Satisfaction Task Force served as a focus group to appraise physician job satisfaction measures and other worklife domains (e.g., workload, work-life balance) for their applicability to hospitalists. An expert panel (TBW, KH, CTW) synthesized the focus group's discussion to generate 14 domains most pertinent to current hospitalist job satisfaction which were further refined through multiple discussions in the focus group.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…7 Previous reports examining physician satisfaction and burnout by career stage suggest that the prevalence of burnout is highest and career satisfaction is lowest in early-to mid-career phases, 4 yet these reports aggregated multiple professions despite the distinct demographic characteristics of pediatricians (including gender and income differences). 8,9 Although some investigations have examined relationships between physician and practice characteristics associated with personal and career satisfaction, 10,11 balance, 12 and avoidance of burnout, 13 the extent to which these relationships apply to pediatricians is largely unknown. 7 In particular, early career pediatricians are especially vulnerable because they experience multiple transitions personally (such as having new children) and professionally (including new jobs after training) and represent the future of the pediatric workforce.…”
mentioning
confidence: 99%
“…Scheurer et al [16] also found the same problems about facilities. Physicians said that CDMP can be done only in 1 day, but because the laboratory result did not come out in the same day so the doctor have to examine the patient the other day.…”
Section: Discussionmentioning
confidence: 67%